Coordination of wind turbines and synchronous generators for system frequency control. (December 2018) - Xu, Guoyi; Liu, Fanglei; Hu, Jiaxin; Bi, Tianshu
Abstract: Variable speed wind turbines provide temporary frequency support by releasing kinetic energy, this lasts only a few seconds. The coordination with the synchronous generators in the system is required to improve the frequency control performance of the system. In this study, a low limit of the rotor speed of the wind turbines is implemented to reduce the large mechanical power drop during the frequency control. The power shape of releasing the wind turbine kinetic energy and the coordination of the control between the wind turbines and the synchronous generators are proposed. The kinetic energy of the wind turbines is used to reduce the rate of change of frequency and the synchronous generators are controlled to produce additional power to assist with the recovery of the frequency and the wind turbines' rotor speed. A simulation analysis using Matlab/Simulink was conducted to illustrate the effectiveness of the proposed control strategy. The results show a significant improvement in the frequency control and demonstrate the stable operation of the wind turbines. As a result, the stability of the power system is maintained under high penetration of wind power. Highlights: Coordinate control can reduce ROCOF, frequency nadir and speed up frequency recover. The proposed power shape will reduce ROCOF and avoid the second frequency drop. Minimum rotor speed will increase output power and improve frequency control effect.